Computer-aided detection (CAD) system for personalized disease detection, assessment, and tracking, in medical imaging based on user selectable criteria - WAHL RICHARD L; LEAL JEFFREY (2015)
An embodiment of the current invention includes computer-implemented method for image processing. The method includes receiving a first medical image from a data storage device, the first medical image comprising a plurality of image voxels and representing a plurality of tissue regions of a subject; automatically determining a reference value based on the first medical image, the reference value capable of providing a range of background level of voxel intensity values within at least one non-disease tissue region of the subject; generating a disease threshold based on the reference value; identifying portions of the medical image corresponding to disease-tissue regions according to the disease threshold, each of the portions comprising a plurality of connected image voxels in the medical image; and entering data encoding the disease-tissue regions into a database for subsequent comparisons.